2013
DOI: 10.1016/j.febslet.2013.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of sarcolipin decreases the energy requirements for Ca2+ transport by sarco(endo)plasmic reticulum Ca2+‐ATPases in resting skeletal muscle

Abstract: a b s t r a c tThe purpose of this study was to examine the effects of sarcolipin (SLN) on sarco(endo) plasmic reticulum Ca 2+ -ATPase (SERCA pump) energetics in vivo and resting skeletal muscle metabolic rate. Using SLN knockout (Sln À/À ) mice we show that SLN ablation increases the transport stoichiometry of SERCA pumps (Ca 2+ uptake/Ca 2+ -ATPase activity) and decreases the relative contribution of SERCA pumps to resting oxygen consumption (VO 2 ) in soleus without affecting soleus or whole body VO 2 . The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 27 publications
3
83
3
Order By: Relevance
“…These data suggest that SLN provides additional regulatory control over Ca 2+ handling properties in human cardiac muscle, particularly in regions such as the atria where PLN is absent and under conditions of elevated Ca 2+ concentration (Sahoo et al 2013). Recent evidence also suggests that SLN, but not PLN, may play a role in thermal regulation by promoting uncoupling of the SERCA pump; however, this evidence will be reviewed in the section outlining the regulatory mechanisms of SERCA1a (Bal et al 2012;Sahoo et al 2013;Bombardier et al 2013;Gamu et al 2014).…”
Section: The Role Of Sarcolipin In Regulating Serca2amentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that SLN provides additional regulatory control over Ca 2+ handling properties in human cardiac muscle, particularly in regions such as the atria where PLN is absent and under conditions of elevated Ca 2+ concentration (Sahoo et al 2013). Recent evidence also suggests that SLN, but not PLN, may play a role in thermal regulation by promoting uncoupling of the SERCA pump; however, this evidence will be reviewed in the section outlining the regulatory mechanisms of SERCA1a (Bal et al 2012;Sahoo et al 2013;Bombardier et al 2013;Gamu et al 2014).…”
Section: The Role Of Sarcolipin In Regulating Serca2amentioning
confidence: 99%
“…Specifically, SLN affects the maximal SERCA-mediated Ca 2+ uptake (V max ) even at high Ca 2+ concentrations, and interacts with SERCA1a throughout the kinetic cycle (Sahoo et al 2013). While SLN was originally considered to be a PLN analogue that regulated SERCA1a in skeletal muscle, recent studies have demonstrated a potential role of SLN in regulating skeletal muscle thermogenesis and whole-body energy metabolism by promoting uncoupling of Ca 2+ transport and ATP hydrolysis (Bal et al 2012;Bombardier et al 2013;Gamu et al 2014). It is suggested that SLN and Ca 2+ bind to SERCA simultaneously, promoting uncoupling of the pump and increasing total energy expenditure (Bal et al 2012;Gamu et al 2014).…”
Section: Sarcolipin Regulates the Activity Of Serca1mentioning
confidence: 99%
“…This proportion can be further modified by the SERCA regulatory protein sarcolipin (SLN) (Bombardier et al. 2013b). …”
Section: Introductionmentioning
confidence: 99%
“…2006) and a recent physiological study (Bombardier et al. 2013b) have shown that SLN can uncouple Ca 2+ transport from ATP hydrolysis, increasing the energy demand by SERCA to pump Ca 2+ . SLN can promote SERCA inefficiency across a range of metabolic rates (Gamu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Student's t tests were used to compare sAnk1 (WT) and sAnk1 mutant, sAnk1 (all-L), for co-IP and AFRET experiments with p Ͻ 0.05 being considered significant. Results of assays of ATPase activity were fit to the equation for an allos- (76,77), from data acquired in four experiments conducted on microsomes from three independent transfections. K Ca2ϩ ([Ca 2ϩ ] free resulting in half-maximal activation) was calculated using nonlinear regression analysis.…”
Section: Methodsmentioning
confidence: 99%